197k views
1 vote
What is the first step to solve the equation:
11 - 3x = 44

What is the first step to solve the equation: 11 - 3x = 44-example-1
User Jnosek
by
4.8k points

2 Answers

1 vote

11-3x=44

One solution was found :

x = -11

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

11-3*x-(44)=0

Step by step solution :

Step 1 :

Pulling out like terms :

1.1 Pull out like factors :

-33 - 3x = -3 • (x + 11)

Equation at the end of step 1 :

Step 2 :

Equations which are never true :

2.1 Solve : -3 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation :

2.2 Solve : x+11 = 0

Subtract 11 from both sides of the equation :

x = -11

One solution was found :

x = -11

Processing ends successfully

User Ryan Morlok
by
5.7k points
2 votes

Answer:

C.

Explanation:

You want to try to isolate the coefficient. In order to do so, you want to subtract 11 from both sides.

User Dertseha
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.